IL-21 in Conjunction with Anti-CD40 and IL-4 Constitutes a Potent Polyclonal B Cell Stimulator for Monitoring Antigen-Specific Memory B Cells - Fridolin Franke; Greg A. Kirchenbaum; Stefanie Kuerten; Paul V. Lehmann (Cells, 2020)
Detection of antigen-specific memory B cells for immune monitoring requires their activation, and is commonly accomplished through stimulation with the TLR7/8 agonist R848 and IL-2. To this end, we evaluated whether addition of IL-21 would further enhance this TLR-driven stimulation approach; which it did not. More importantly, as most antigen-specific B cell responses are T cell-driven, we sought to devise a polyclonal B cell stimulation protocol that closely mimics T cell help. Herein, we report that the combination of agonistic anti-CD40, IL-4 and IL-21 affords polyclonal B cell stimulation that was comparable to R848 and IL-2 for detection of influenza-specific memory B cells. An additional advantage of anti-CD40, IL-4 and IL-21 stimulation is the selective activation of IgM+ memory B cells, as well as the elicitation of IgE+ ASC, which the former fails to do. Thereby, we introduce a protocol that mimics physiological B cell activation through helper T cells, including induction of all Ig classes, for immune monitoring of antigen-specific B cell memory.